Stabilizing institutions for new venture investment decisions. Issue 4 (12th October 2015) - Crum, Michael; Nelson, Thomas E.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to examine the relationship between aspects of a country's institutional environment and entrepreneurial investors' overall rate of return. Design/methodology/approach – Specifically, monetary stability and property rights are tested against both entrepreneurs' and angel investors' expected financial returns and payback periods, respectively. Data from the Global Entrepreneurship Monitor survey including years 2004 through 2006 and encompassing 50 countries are aggregated and examined using random coefficient multilevel modeling. Findings – We find that strong property rights encourage both angel investors and entrepreneurs to invest in new ventures with longer payback periods and encourage angel investors to invest in ventures with lower expected financial returns. Practical implications – This suggests that one key to increasing entrepreneurial investment in a country is to guarantee strong property rights. Therefore, both entrepreneurs seeking funding and countries seeking entrepreneurs should incorporate property rights issues into their decision-making. Originality/value – This finding moves the "attracting entrepreneurs" conversation beyond the typical tax-abatement, infrastructure building, business cluster recommendations prevalent in academic and professional literature and points to one of the more fundamental reasons entrepreneurial "cultures" develop some places, but not others.